UJI KARAKTERISTIK 4 JENIS RAMBUTAN LOKAL (Nephelium sp.) - Nur Hasanah Nasution; T. Rosmawaty; Mardaleni (DINAMIKA PERTANIAN, 2018)
ABSTRACT The purpose of this study was to determine and compare the Morphological, Physical, Storage, and Chemical Characteristics of 4 types of Local Rambutan (Nephelium Sp.). Fruit characteristic test is carried out on Morphology, Physical Properties, Storing Power, and Chemical Content of Rambutan fruit which refers to Descriptor of Rambutan (IPGRI, 2003). This study uses one-way Anova Analysis which is then tested further by BNJ at a 5% level for the Chemical Content Test of fruit. Followed by Klastering Test using MVSP 32 Program with Spearman Coefficient analysis. Morphological observations of fruit quantitatively and qualitatively that is Pulasan has the character of weight, length, diameter, skin weight, aryl weight, and weight of fruit seeds is greater than other types. Lulu has a uniform fruit skin color that is dark red, Sipadeh (N2) also has a uniform color that is yellow / cream. Sipadeh (N1) and Pulasan have a sweeter taste and easier idleness (chipped). This is different from Lulu and Sipadeh (N2), where both types have a sour taste and are difficult to crack (peel) from the seeds. In the chemical test, Sipadeh (N2) and Lulu have a high content of Vitamin C and total titrated acid. Whereas Pulasan and Sipadeh (N1) which have high Dissolved Solid Total Value. The results of the morphological cluster analysis of the fruit produced a dendrogram with a phenolic similarity of -50% to 100%. The results of the cluster chemical analysis result in a dendrogram with Kf -80% to 70%. Keyword: Characteristics, Local Rambutan (Nephelium Sp.)